Process approach in teaching science for the educable mentally retarded intermediate level - Villabona, Fe Bagares 1947-; Sison, Waldetrudes Montojo (1972)
The preparation of the study grew out from the question on how the Process Approach can be effectively adapted in the teaching of science for the educable mentally retarded in the intermediate level. The study employed the library research method. The researcher found out that the process approach or inductive discovery technique may be used to uplift science instruction for the educable mentally retarded.
Vita.
Thesis (Master of Arts in Teaching - Special Education : Mental Retardation)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines; Children with mental disabilities -- Education (Elementary) -- Philippines; Special education -- Philippines